Prevalence of near-death experiences in people with and without REM sleep intrusion - Daniel Kondziella; Jens P. Dreier; Markus Harboe Olsen (PeerJ, 2019)
Background The origin and prevalence of near-death experiences are unknown. A recent study suggested a link with REM sleep intrusion but was criticized for its selection of control participants. We therefore assessed the association of REM intrusion and near-death experiences with different methods. Methods Using a crowd-sourcing platform, we recruited 1,034 lay people from 35 countries to investigate the prevalence of near-death experiences and self-reported REM sleep intrusion. Reports were validated using the Greyson Near-Death Experiences Scale (GNDES) with ≥7 points as cut-off for near-death experiences. Results Near-death experiences were reported by 106 of 1,034 participants (10%; 95% CI [8.5–12%]). Evidence of REM intrusion was more common in people with near-death experiences (n = 50∕106; 47%) than in people with experiences with 6 points or less on the GNDES (n = 47∕183; 26%) or in those without such experiences (n = 107∕744; 14%; p =  < 0.0001). Following multivariate regression analysis to adjust for age, gender, place of residence, employment and perceived danger, this association remained highly significant; people with REM intrusion were more likely to exhibit near-death experiences than those without (OR 2.85; 95% CI [1.68–4.88]; p = 0.0001). Discussion Using a crowd-sourcing approach, we found a prevalence of near-death experiences of 10%. While age, gender, place of residence, employment status and perceived threat do not seem to influence the prevalence of near-death experiences, we confirmed a possible association with REM sleep intrusion.